Educational exchange in thyroid core needle biopsy diagnosis: enhancing pathological interpretation through guideline integration and peer learning - Agnes Stephanie Harahap; Chan Kwon Jung (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
Background While fine needle aspiration cytology (FNAC) plays an essential role in the screening of thyroid nodules, core needle biopsy (CNB) acts as an alternative method to address FNAC limitations. However, diagnosing thyroid CNB samples can be challenging due to variations in background and levels of experience. Effective training is indispensable to mitigate this challenge. We aim to evaluate the impact of an educational program on improving the accuracy of CNB diagnostics. Methods The 2-week observational program included a host mentor pathologist with extensive experience and a visiting pathologist. The CNB classification by The Practice Guidelines Committee of the Korean Thyroid Association was used for the report. Two rounds of reviewing the case were carried out, and the level of agreement between the reviewers was analyzed. Results The first-round assessment showed a concordance between two pathologists for 247 thyroid CNB specimens by 84.2%, with a kappa coefficient of 0.74 (indicating substantial agreement). This finding was attributed to the discordance in the use of categories III and V. After peer learning, the two pathologists evaluated 30 new cases, which showed an overall improvement in the level of agreement. The percentage of agreement between pathologists on thyroid CNB diagnosis was 86.7%, as measured by kappa coefficient of 0.80. Conclusions This educational program, consisting of guided mentorship and peer learning, can substantially enhance the diagnostic accuracy of thyroid CNB. It is useful in promoting consistent diagnostic standards and contributes to the ongoing development of global pathology practices.